The University of the Philippines Institute of Library Science curriculum and the needs of business and industry - Ouano, Val Rico Rommel G. (1998)
This study deals with the University of the Philippines Institute of Library Science curriculum and how relevant and useful its courses are in the performance of librarians and information professionals in a special library. The special libraries chosen are in 50 private business and industry corporations in Makati City.